Diversity of virulence factors associated with West Australian methicillin-sensitive staphylococcus aureus isolates of human origin - Waryah, Charlene Babra; Gogoi-Tiwari, Jully; Wells, Kelsi; Eto, K.; Masoumi, E.; Costantino, Paul; Kotiw, M.; Mukkur, T. (Hindawi Publishing Corporation, 2016)
An extensive array of virulence factors associated with S. aureus has contributed significantly to its success as a major nosocomial pathogen in hospitals and community causing variety of infections in affected patients. Virulence factors include immune evading capsular polysaccharides, poly-N-acetyl glucosamine, and teichoic acid in addition to damaging toxins including hemolytic toxins, enterotoxins, cytotoxins, exfoliative toxin, and microbial surface components recognizing adhesive matrix molecules (MSCRAMM). In this investigation, 31 West Australian S. aureus isolates of human origin and 6 controls were analyzed for relative distribution of virulence-associated genes using PCR and/or an immunoassay kit and MSCRAMM by PCR-based typing. Genes encoding MSCRAMM, namely, Spa, ClfA, ClfB, SdrE, SdrD, IsdA, and IsdB, were detected in >90% of isolates. Gene encoding a-toxin was detected in >90% isolates whereas genes encoding ß-toxin and SEG were detectable in 50-60% of isolates. Genes encoding toxin proteins, namely, SEA, SEB, SEC, SED, SEE, SEH, SEI, SEJ, TSST, PVL, ETA, and ETB, were detectable in >50% of isolates. Use of RAPD-PCR for determining the virulence factor-based genetic relatedness among the isolates revealed five cluster groups confirming genetic diversity among the MSSA isolates, with the greatest majority of the clinical S. aureus (84%) isolates clustering in group IIIa.